The Psychometric Properties of Translating Self-Efficacy Belief: Perspectives From Chinese Learners of Translation - Yang, Yanxia; Cao, Xinyu; Huo, Xing (Frontiers in Psychology, 2021)
Understanding learners’ translating self-efficacy belief is helpful to predict their coping abilities and translation performance. However, the assessment of learners’ translating self-efficacy has been largely overlooked in translation research. The purpose of this study is to develop and validate an instrument to examine the translating self-efficacy belief in a sample of Chinese translation learners. Scale items were collected and refined based on an expert-panel consensus opinion. Exploratory factor analysis and confirmatory factor analysis across two independent samples (Sample I=193, Sample II=247) revealed and validated a three-dimensional structure: efficacy in internal competence, efficacy in psycho-physical competence and efficacy in external competence. The findings provide supporting evidence for the scale application in translator education context.